Green gap in GaN-based light-emitting diodes: in perspective. Issue 5 (3rd September 2021) - Usman, Muhammad; Munsif, Munaza; Mushtaq, Urooj; Anwar, Abdur-Rehman; Muhammad, Nazeer
Abstract: Significant progress has been made in the advancement of light-emitting devices in both the blue and the red parts of the emission spectrum. However, the quantum efficiency of green light-emitting diodes is still significantly lower as compared to blue- and red-emitting devices. This efficiency lag is commonly known as the "green gap" in the solid-state lighting industry. The efficiency issues in the green emission spectrum restrain further advancement in solid-state lighting. A combination of efficient blue, green, and red light-emitting devices is a promising solution toward efficient white light-emitting diodes. Despite the efficiency gap in the green emission, the lighting industry continues to produce relatively efficient white light-emitting diodes using down-conversion phosphors. However, the fruits of the solid-state white lighting could be fully achieved through color-mixing approaches rather through phosphor-based conversion. Therefore, to produce efficient green light-emitting diodes, their inherent issues such as the density of different types of defects and internal electric field should be reduced. In this study, we review various challenges and prospects of green light-emitting diodes. Broadly, the first part of this review explains the complex factors that degrade the performance of InGaN/GaN multiquantum well green light-emitting diodes, whereas the second part focuses on different strategies to enhance the internal quantum efficiency of green light-emitting diodes.